2010
DOI: 10.1111/j.1600-0897.2010.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW ARTICLE: Immunology of Pre‐Eclampsia

Abstract: Citation Redman CWG, Sargent IL. Immunology of Pre‐eclampsia. Am J Reprod Immunol 2010Pre‐eclampsia develops in stages, only the last being the clinical illness. This is generated by a non‐specific, systemic (vascular), inflammatory response, secondary to placental oxidative stress and not by reactivity to fetal alloantigens. However, maternal adaptation to fetal (paternal alloantigens) is crucial in the earlier stages. A pre‐conceptual phase involves maternal tolerization to paternal antigens by seminal plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
505
2
23

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 612 publications
(553 citation statements)
references
References 71 publications
23
505
2
23
Order By: Relevance
“…In a recent meta-analysis by Thangaratinam et al (40), the rate of pregnancy complications has been linked to thyroid autoimmunity showing significantly higher rates of complications in antibody positive women than in antibody negative controls, despite biochemical euthyroidism. Interaction of TSH receptor autoantibodies with receptors for gonadotrophins may represent one mechanism to explain the increased prevalence of problems in pregnancies of mothers with autoimmune thyroid disease, but a number of other mechanisms including associated immune dysregulation targeting particularly the reproductive tract and/or the foeto-placental unit have been discussed (41,42). This is confirmed by a recent larger prospective study that has shown a stepwise increase in miscarriage rates with thyroid autoimmunity alone and in combination with SCH (43).…”
Section: Evidence For Adverse Effects Of Sch During Pregnancysupporting
confidence: 69%
“…In a recent meta-analysis by Thangaratinam et al (40), the rate of pregnancy complications has been linked to thyroid autoimmunity showing significantly higher rates of complications in antibody positive women than in antibody negative controls, despite biochemical euthyroidism. Interaction of TSH receptor autoantibodies with receptors for gonadotrophins may represent one mechanism to explain the increased prevalence of problems in pregnancies of mothers with autoimmune thyroid disease, but a number of other mechanisms including associated immune dysregulation targeting particularly the reproductive tract and/or the foeto-placental unit have been discussed (41,42). This is confirmed by a recent larger prospective study that has shown a stepwise increase in miscarriage rates with thyroid autoimmunity alone and in combination with SCH (43).…”
Section: Evidence For Adverse Effects Of Sch During Pregnancysupporting
confidence: 69%
“…Moreover, if the association of Ang-1/Ang-2 ratio with inflammation was stronger in these diseases then that may explain why elevated ratios are associated with pregnancy outcomes that are known to have inflammation as part of their pathogenesis, such as preterm birth, preeclampsia and miscarriage. [25][26][27] Our results suggest that the Ang-1/Ang-2 ratio may be a promising biomarker for miscarriage. Especially as women with recurrent miscarriage have reduced blood vessel expression of Ang-2 related to premature advanced vessel maturation.…”
mentioning
confidence: 83%
“…After conception, regulatory T cells, interacting with indoleamine 2,3-dioxygenase, together with decidual NK cell recognition of fetal HLA-C on extravillous trophoblast may facilitate placental growth by immunoregulation. Complete failure of this mechanism would cause miscarriage, while partial failure would cause poor placentation and dysfunctional uteroplacental perfusion [8]. Bayram et al found that the patient with severe preeclampsia have higher values of IL-6 and IL-1β when compared to the normotensive ones [9].…”
Section: Introductionmentioning
confidence: 99%